Immobilization Of Lipase From Candida Rugosa Using Alginate Bead - Azeman, Nursyarinie Nabihah (Universiti Sains Malaysia, 2018)
Applications of enzyme in industry are becoming more relevant these days. In an effort to increase the application of enzyme, several techniques have been introduced in the research. In the present work, lipase from Candida rugosa was immobilized on alginate beads for possible applications. The enzyme was entrapped by drop-wise addition of an aqueous mixture of sodium alginate and the biocatalyst to the hardening solution of calcium ion. Effect of alginate concentration, lipase concentration, temperature at optimum conditions and reusability of the enzyme were investigated. An increased in alginate concentration give higher unit activity of the enzyme. This techniques provided gives higher immobilization yield (%) and activity yield at 99.17% and 2.365 IU/mg respectively. Under optimal conditions generate by ANOVA analysis using Design of Experiment (DoE) software ( 0.03 g/ml of lipase concentration and 2% of alginate concentration), the lipase beads retained enzyme activity equivalent to 70.28%. The optimum temperature suitable for immobilized enzyme also studied. Enzyme activity increases when the temperature was increased to 37'C, then decreases at higher temperature. The optimum temperature was determined at 37'C with unit activity of 0.331 IU/mg. At temperature 55'C, the activity declined to 0.037 IU/mg which suggested due to denaturation of lipase structure.